Proteomics and kidney stone disease - V. Thongboonkerd (2018)
Kidney stone disease (nephrolithiasis) is an ancient and common affliction. It has been recognized for a long time with evidence of stone found in ∼7,000-year-old mummies and remains a common problem worldwide, indicating ineffective prevention in the past. Precise pathogenic and molecular mechanisms of kidney stone formation are still poorly understood and should be further elucidated. Also, identification of novel therapeutic targets for better therapeutic outcome and successful prevention of the occurrence and recurrence of the stone are crucially required. One of the most promising tools for current and future biomedical research is proteomics, which has been extensively and widely applied to the nephrology field during the past 5 years. Its high-throughput capability holds a great promise also to kidney stone research. This chapter provides a brief overview of proteomic methodologies recently used for the investigation of nephrolithiasis and recent proteomic studies of nephrolithiasis are summarized. Copyright © 2008 S. Karger AG.